Ukuran Perusahaan dan Kinerja Lingkungan Perusahaan Terhadap Munculnya Asimetri Informasi Menggunakan Pengungkapan ESG sebagai Variabel Moderasi - Rafli Syahrul Hikam; Tantina Haryati (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the analysis of environmental (social), and governance (ESG) disclosure as a variable moderating the relationship between company size and environmental performance on the emergence of information asymmetry. This research method uses quantitative methods, and the data used is secondary data. The research was conducted on basic materials sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sample used is 150 annual reports from 30 companies with a period of 5 years. The data source used comes from the annual report. The research data was processed and analyzed using Warp PLS 7.0 software with the PLS-SEM analysis method. The results showed that a) the variable firm size for information asymmetry has a probability value of 0.209 with a path coefficient of 0.065; b) the environmental performance variable on information asymmetry has a probability value of 0.071 with a path coefficient of -0.117; c) the environmental social governance variable that moderates firm size towards information asymmetry has a probability value of 0.022 with a path coefficient of -0.159; d) the environmental social governance disclosure variable that moderates environmental performance on information asymmetry has a probability value of 0.458 with a path coefficient of -0.009. In conclusion, company size has no significant and positive effect on the emergence of information asymmetry, and company environmental performance does not have a significant negative effect on the emergence of information asymmetry. In addition, ESG has a significant and negative effect in moderating firm size on the emergence of information asymmetry, while ESG has no and negative effect in moderating environmental performance on the emergence of information asymmetry. Keywords: Information Asymmetry, ESG, Environmental Performance, Company Size